(untitled) (Research, Society and Development, 2025)
Objective: To present demographic, socioeconomic, epidemiological, governance and pharmaceutical services management data and information in the municipality of Belém, Pará. Methodology: This is an exploratory, descriptive and analytical study, retrospective for the years 2020 to 2024. Results: The municipality of Belém has an estimated population of 1,303,403 inhabitants; GDP per capita of R 33,055.36; Schooling rate for 6 to 14 years of age of 96%; HDI-M of 0.628; Gini index of 0.746; Infant mortality rate of 27.6 deaths per thousand births. Regarding the Institutionalization of Pharmaceutical Assistance, the municipality partially meets the indicators related to the dimensions of human resources, governance, planning and management, structure and organization, sectoral policies and technical-managerial actions and technical-assistance actions. Conclusion: There are problems to be overcome in the context of Pharmaceutical Assistance regarding the dimensions of human resources, governance, planning, management, structure, organization, sectoral policies, technical-managerial actions and technical-assistance actions. Additional efforts need to be made to improve, monitor and evaluate the governance, planning and management process, aiming to qualify programs, actions, activities and tasks inherent to the provision of effective, efficient and sustainable Pharmaceutical Assistance.